Gomella's neonatology: Management, procedures, on - call problems, diseases and drugs - Gomella, Tricia Lacy (McGraw Hill, 2020)
A true essential for nearly three decades, this streamlined pocket reference provides logically organized, quickly retrievable information on basic and advanced management techniques for the neonate. Featuring a convenient outline approach that puts key information at reader's fingertips, this quick reference covers everything clinicians need to know about on-call neonatal problems, procedures, diseases and disorders, and pharmacology.